Alterations in Oral Microbiota of Differentiated Thyroid Carcinoma Patients With Xerostomia After Radioiodine Therapy - Lin, Baiqiang; Zhao, Fuya; Liu, Yang; Sun, Jiayu; Feng, Jing; Zhao, Lei; Wang, Haoran; Chen, Hongye; Yan, Wei; Guo, Xiao; Shi, Shang; Li, Zhiyong; et al. (Frontiers in Endocrinology, 2022)
Background and Aims: Oral xerostomia remains one of the most common complications of differentiated thyroid carcinoma patients (DTC) after radioiodine therapy (RAI). Environmental factors in the etiology of xerostomia are largely unknown. We aimed to characterize the oral microbiota signatures and related biological functions associated with xerostomia and identify environmental factors affecting them. Methods: Saliva was collected from 30 DTC patients with xerostomia (XAs), 32 patients without xerostomia (indicated as non-XAs) following RAI after total thyroidectomy, and 40 healthy people (HCs) for 16S rRNA sequencing analysis. Results: The oral microbiota of XAs and non-XAs exhibited significant differences in α and β diversities and bacterial taxa. The abundance of porphyromonas, fusobacterium, and treponema_2 was significantly higher in XAs, while the abundance of the streptococcus was lower in the microbiota of non-XAs. Fusobacterium, and porphyromonas were positively correlated with unstimulated/stimulated whole salivary secretion (USW)/(SWS), while fusobacterium, porphyromonas, and treponema_2 genera levels were positively associated with cumulative dose. Phylogenetic investigation of communities by reconstruction of unobserved states (PICRUSt2) and BugBase suggested a significant difference in the expression of potentially_pathogenic, anaerobic, gram_negative, the arachidonic acid metabolism, and lipopolysaccharide (LPS) biosynthesis between XAs and non-XAs, possibly interdependent on radioiodine-induced inflammation. NetShift analysis revealed that porphyromonas genus, might act as key drivers during the process of xerostomia. Five genera effectively distinguished XAs from non-XAs (AUC = 0.87). Conclusion: Our study suggests for the first time that DTC patients with xerostomia after RAI display microbiota profiles and associated functional changes that may promote a pro-inflammatory environment. Dysbiosis of the oral microbiota may contribute to exacerbating the severity of xerostomia. Our results provide a research direction of the interaction mechanism between oral microbiota alteration and the progress of xerostomia.